Gender Categories in English and Uzbek: A Corpus-Based Comparative Typological Analysis - Tolibova Shoxzoda Baxtiyorovna (Indonesian Journal Publisher, 2026)
The study explores the linguistic representation of gender categories in English and Uzbek through a corpus-based comparative typological approach. Gender has become an important topic in contemporary linguistics, as language not only reflects social structures but also contributes to the construction of social identities. The research examines the semantic and functional behavior of gender-related lexical units in two languages that belong to different linguistic families and cultural traditions. Data for the analysis were obtained from large language corpora, including the Corpus of Contemporary American English (COCA) and the British National Corpus for English, as well as available Uzbek language corpora and digital text collections. The analysis focuses on several key gender-related lexical items such as woman, man, gender, masculinity, femininity, and their Uzbek equivalents. Quantitative and qualitative methods were used to investigate frequency patterns, collocational behavior, and contextual usage. The results reveal both similarities and differences in the linguistic representation of gender categories. While English demonstrates a broader range of discourse contexts related to gender identity and social roles, Uzbek usage patterns appear to be more closely linked to cultural and social norms. The findings contribute to comparative linguistics and gender studies by providing empirical evidence about the ways gender categories are encoded in two typologically different languages. The study also highlights the importance of corpus-based methods in identifying linguistic patterns that might not be immediately visible through traditional qualitative analysis.